Integrated transgene and transcriptome reveal the molecular basis of MdWRKY87 positively regulate adventitious rooting in apple rootstock - Tian, Qiuye; Xu, Mengli; Wu, Dongchen; Wang, Chaoping; Wang, Xianlin; Che, Qinqin; Li, Zhengnan; Xu, Xiaozhao (Frontiers in Plant Science, 2023)
For most fruit and forest species vegetative propagated from elite genotypes, adventitious rooting is essential. The ability to form adventitious roots significantly decreased during the juvenile to adult phase change. Apart from the miR156-SPL pathway, whether there is another regulation mechanism controlling age-dependent adventitious rooting ability remained largely unknown. In the present study, we showed that MdWRKY87 expression level was positively correlation with adventitious rooting ability. In addition, over-expressing of MdWRKY87 in tobacco leads to enhanced adventitious rooting ability, more adventitious root number and accelerated adventitious rooting process. Comparative transcriptome profiling indicated that MdWRKY87 overexpression can activate the expression of adventitious rooting-induced genes, such as WOX11 and AIL. In addition, MdWRKY87 overexpression can inhibit the transcription of adventitious rooting-repressed genes, such as AUX/IAAs and RRs. Collectively, here we demonstrated that higher expression level of MdWRKY87 contributing to age-dependent adventitious rooting-competent in juvenile apple rootstock.